DIMENSI GENDER DALAM NOVEL GELANG GIOK NAGA (KAJIAN SASTRA FEMINIS) (Martabat: Jurnal Perempuan dan Anak, 2017)
Gender is the role diversifications, functions, and responsibilities between men and women that formed by social construction and may change with the times. The violence affecting women is mainly due to gender bias in the society. Literature can be used as an effective medium to fight for gender equality as results of discrimination, oppression, marginalizing the position of women because of patriarchal culture in society. Women writers try to fight for their rights to be equal to men through the female figure imagery creation who are struggling to gain the recognition. This is what the goal of liberal feminism seeks to eliminate discrimination and social inequality on gender mainly lies in education and employment. The female characters in Gelang Giok Naga novel get discriminatory treatment as a result of famialism which only positions women as wives, house wives, and mothers so that there is a role gap.   Kata kunci: gender, novel, sastra, kajian feminisme